Cardiovascular drugs and COVID‐19 clinical outcomes: A living systematic review and meta‐analysis. Issue 12 (7th July 2021) - Asiimwe, Innocent G.; Pushpakom, Sudeep; Turner, Richard M.; Kolamunnage‐Dona, Ruwanthi; Jorgensen, Andrea L.; Pirmohamed, Munir
Abstract : Aims: The aim of this study was to continually evaluate the association between cardiovascular drug exposure and COVID‐19 clinical outcomes (susceptibility to infection, disease severity, hospitalization, hospitalization length, and all‐cause mortality) in patients at risk of/with confirmed COVID‐19. Methods: Eligible publications were identified from more than 500 databases on 1 November 2020. One reviewer extracted data with 20% of the records independently extracted/evaluated by a second reviewer. Results: Of 52 735 screened records, 429 and 390 studies were included in the qualitative and quantitative syntheses, respectively. The most‐reported drugs were angiotensin‐converting enzyme inhibitors (ACEIs)/angiotensin receptor blockers (ARBs) with ACEI/ARB exposure having borderline association with confirmed COVID‐19 infection (OR 1.14, 95% CI 1.00–1.31). Among COVID‐19 patients, unadjusted estimates showed that ACEI/ARB exposure was associated with hospitalization (OR 1.76, 95% CI 1.34–2.32), disease severity (OR 1.40, 95% CI 1.26–1.55) and all‐cause mortality (OR 1.22, 95% CI 1.12–1.33) but not hospitalization length (mean difference −0.27, 95% CI −1.36–0.82 days). After adjustment, ACEI/ARB exposure was not associated with confirmed COVID‐19 infection (OR 0.92, 95% CI 0.71–1.19), hospitalization (OR 0.93, 95% CI 0.70–1.24), disease severity (OR 1.05, 95% CI 0.81–1.38) or all‐cause mortality (OR 0.84, 95% CI 0.70–1.00). Similarly, subgroup analyses involving only hypertensive patients revealed that ACEI/ARB exposure was not associated with confirmed COVID‐19 infection (OR 0.93, 95% CI 0.79–1.09), hospitalization (OR 0.84, 95% CI 0.58–1.22), hospitalization length (mean difference −0.14, 95% CI −1.65–1.36 days), disease severity (OR 0.92, 95% CI 0.76–1.11) while it decreased the odds of dying (OR 0.76, 95% CI 0.65–0.88). A similar trend was observed for other cardiovascular drugs. However, the validity of these findings is limited by a high level of heterogeneity and serious risk of bias. Conclusion: Cardiovascular drugs are not associated with poor COVID‐19 outcomes in adjusted analyses. Patients should continue taking these drugs as prescribed.